Faktor-faktor penentu minat beli produk di e-commerce - Margie Sabina Ranti; Ari Setiyaningrum (Jurnal Manajemen Maranatha, 2022)
This study aims to examine the effect of electronic of mouth (e-WOM) on purchase intention which is mediated by attitude towards the brand and brand image. The research model was tested in the Tokopedia e-commerce context. Primary data were collected using a survey method by distributing questionnaires to 100 respondents. Purposive sampling technique was used as the basis for determining sampling in this study. The results of hypothesis testing using SEM-PLS indicated that e-WOM directly and positively affects purchase intention, e-WOM positively affects attitudes towards brands and brand image, as well as attitudes towards brands and brand image positively affects purchase intention. The results of the mediation test prove that attitudes towards the brand and brand image partially mediate the effect of e-WOM on purchase intention.